2015
DOI: 10.1039/c5cp05213k
|View full text |Cite
|
Sign up to set email alerts
|

Panoscopically optimized thermoelectric performance of a half-Heusler/full-Heusler based in situ bulk composite Zr0.7Hf0.3Ni1+xSn: an energy and time efficient way

Abstract: All scale hierarchical architecturing, matrix/inclusion band alignment and intra-matrix electronic structure engineering, the so called panoscopic approach for thermoelectric materials has been demonstrated to be an effective paradigm for optimizing high ZT. To achieve such hierarchically organized microstructures, composition engineering has been considered to be an efficient strategy. In this work, such a panoscopic concept has been extended to demonstrate for the first time in the case of half-Heusler based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 95 publications
6
30
0
Order By: Relevance
“…Especially, this value is lower than those of the alloyed samples at~13 W m -1 K -1 for Zr 0.9 Ti 0.1 NiSn and~6 W m -1 K -1 for Zr 0.7 Ti 0.3 Ni 1.03 Sn [20,29]. The lowest lattice thermal conductivity is~3.4 W m -1 K -1 at 973 K for ZrNi 1.13 Sn 1.03 , suggesting the effective medium-to-high frequency phonon scattering [16,36,37].…”
Section: Researchmentioning
confidence: 56%
See 4 more Smart Citations
“…Especially, this value is lower than those of the alloyed samples at~13 W m -1 K -1 for Zr 0.9 Ti 0.1 NiSn and~6 W m -1 K -1 for Zr 0.7 Ti 0.3 Ni 1.03 Sn [20,29]. The lowest lattice thermal conductivity is~3.4 W m -1 K -1 at 973 K for ZrNi 1.13 Sn 1.03 , suggesting the effective medium-to-high frequency phonon scattering [16,36,37].…”
Section: Researchmentioning
confidence: 56%
“…Since the half-Heusler phase has superior TE properties, more studies are focusing on the boundary of the half-Heusler site. We pointed out the reported experimental solubility limit in ZrNi 1+x Sn, which is around 0:03 ≤ x ≤ 0:05 at 1100-1200 K [20][21][22]. More differently, Romaka et al found this solubility up to x = 0:3 at 1100 K [23].…”
Section: Researchmentioning
confidence: 65%
See 3 more Smart Citations